Rape seeds as a source of feed and food protein - Nosenko, Tamara; Kot, Tatiana; Kishchenko, Vladimir (My University, 2014)
Amino acid content of proteins, fatty acid composition of oil, glucosinolate content, nutritive value of protein products and functional properties of protein isolates from rape seeds of spring and winter varieties of modern selection were studied in this work. Investigated rape samples were low glucosinolate and low erucic acid content. Tetrachimena piriformis was used for estimation of relative nutritive value of protein products. These values were compared with the same value for casein. Sufficiently high nutritive value (90.1-95.9 %) of winter rape cake, both samples of rape meal and protein isolates were detected. Rape seed protein isolates had high oil binding, emulsifying and foaming capacities. At the same time water holding capacity was lower that of soy protein isolates. We have concluded that protein products from rape seeds of modern selection are important source of feed and food proteins.
Keywords: rape seed; rape protein; amino acids; Tetrachimena piriformis; nutritive value; functional properties; насіння ріпаку; білок ріпаку; Тетрахімена піріформіс; харчова цінність; функціональні властивості; белок рапса; кафедра технології жирів, хімічних технологій харчових добавок та косметичних засобів